Navigating the challenges of invasive pulmonary aspergillosis in lung cancer treatment: a propensity score study - Chin-Wei Kuo; Chien-Yu Lin; Sheng-Huan Wei; Yun-Tse Chou; Chian-Wei Chen; Jeng-Shiuan Tsai; Po-Lan Su; Chien-Chung Lin (Therapeutic Advances in Medical Oncology, 2023)
Background: Invasive pulmonary aspergillosis (IPA) can negatively impact cancer patients’ survival. It remains uncertain whether IPA’s impact on patient outcomes varies by treatment approach in advanced lung cancer. Objectives: To explore the association between IPA and outcomes in patients with advanced lung cancer receiving different treatments. Design: A retrospective cohort study. Methods: We enrolled patients with advanced-stage lung cancer between 2013 and 2021 at a college hospital in Taiwan and used the 2021 European Organization for Research and Treatment of Cancer/Mycoses Study Group Education and Research Consortium consensus for IPA diagnosis. Multivariable logistic regression was used to identify the IPA risk factors. We compared overall survival (OS) and postgalactomannan (GM) test survival between the IPA and control groups using multivariable Cox proportional hazards regression and the Kaplan–Meier method with propensity score matching (PSM). Results: Among 2543 patients with advanced-stage lung cancer, 290 underwent a GM test, of which 34 (11.7%) were diagnosed with IPA. Patients undergoing chemotherapy (HR = 4.02, p = 0.027) and immunotherapy [hazard ratio (HR) = 3.41, p = 0.076] tended to have IPA. Compared to the control group, the IPA group had shorter median OS (14.4 versus 9.9 months, p = 0.030) and post-GM test survival (4.5 versus 1.9 months, p = 0.003). IPA was associated with shorter OS (log-rank p = 0.014 and 0.018 before and after PSM, respectively) and shorter 1-year and 2-year survival post-GM test (HR = 1.65 and 1.66, respectively). Patients receiving chemotherapy or immunotherapy had a shorter post-GM test survival if they had IPA. Conclusions: IPA tended to be diagnosed more frequently in patients receiving chemotherapy or immune checkpoint inhibitors. Patients diagnosed with IPA are associated with shorter survival. Larger cohort studies are needed to verify the observations.